CRIMINAL RESPONSIBILITY TO THE PRODUCERS OF ILLEGAL PCC (PARACETAMOL, CAFEIN, AND CARISOPRODOL) - Peter Wailan Ibrahim; Astutik (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
PCC pills are drugs that have harmful effects on the body, one of its ingredients, carisoprodol is a drug that has been withdrawn from circulation since 2013. In certain cases, PCC pills can cause the body to spasm, go berserk, and act like zombies. From the cases that occur, there arises a problem related to the production of PCC drugs as a crime and its responsibility.